MORTALITY, PRODUCTION AND QUALITY OF EGGS OF DIFFERENT REARING SYSTEMS - Tavares,Bartira de O. (2018)
ABSTRACT The conventional production of eggs in cage systems is intense and compromises the laying hens welfare. More demanding consumer markets have been pushing to abolish the use of cages and thus provide better welfare in poultry laying. This research evaluated the mortality, production, and egg quality of two alternative production systems (free-range and organic free range free-range) and compared them with the conventional system. The research was carried out in two commercial poultry farms and the variables egg weight, shell egg resistance, Haugh unit, mortality and production were recorded during eight months. The results showed that the conventional system presented better production, lower mortality and better shell egg quality. The alternative systems had better internal egg quality. Alternative systems had greater variability in outcomes and problems with disease control, which indicate greater difficulty for proper management.